What lean teaches us about ethics in engineering - Flumerfelt, Shannon (2014)
This theoretical paper provides a comprehensive examination of the need for the ethical development of the engineering student. A review of the literature regarding the need for the teaching of ethics in the Academy and of the need for ethics in the engineering workplace is described. The Toyota Education Model based on respect for people is presented as a viable method for the Academy's consideration.